2020
DOI: 10.21203/rs.2.20377/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Economic Impacts of Retained Placenta and Subclinical Mastitis in Tanzanian Dairy Cows

Abstract: Background: Three dairy farms were investigated for occurrence of retained placenta and subclinical mastitis, and the economic impacts attributable to the conditions. Reproductive performance data from 1169 calvings of dairy cows for five consecutive years spanning from 2014 to 2018 were used in this study. A total of 167 cows were screened with the California Mastitis Test (CMT), and udder quarters with CMT score of ≥ 3 (scale 1–5) were milk sampled for culture and final bacteriological identification. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(72 reference statements)
1
4
0
Order By: Relevance
“…The current findings corroborate with that reported in a recent studies conducted in Rwanda in the same type of farms (55.6%) (Pascal Nyabinwa, Kashongwe, Habimana, Hirwa, & Bebe, 2020) and in Tanzania (51.6%) (Mdegela et al, 2009). The observed prevalence is higher than 38.9% reported in Sudan (Hussein, 2012) 15.0% in Brazilian dairy cows (Ruegg & Pantoja, 2013) and 35.9% obtained in Tanzanian dairy cows (Komba & Kashoma, 2020). However, the present estimate of SCMA prevalence in this study was lower than the previously reported SCMA prevalence in Rwanda (70.2%) (Ndahetuye et al, 2019) Uganda (86.2%) (Abrahmsén, Persson, Kanyima, & Båge, 2014) Kenya (64.0%) (Mureithi & Njuguna, 2016) and Ethiopia (59.2%) (Abebe, Hatiya, Abera, Megersa, & Asmare, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current findings corroborate with that reported in a recent studies conducted in Rwanda in the same type of farms (55.6%) (Pascal Nyabinwa, Kashongwe, Habimana, Hirwa, & Bebe, 2020) and in Tanzania (51.6%) (Mdegela et al, 2009). The observed prevalence is higher than 38.9% reported in Sudan (Hussein, 2012) 15.0% in Brazilian dairy cows (Ruegg & Pantoja, 2013) and 35.9% obtained in Tanzanian dairy cows (Komba & Kashoma, 2020). However, the present estimate of SCMA prevalence in this study was lower than the previously reported SCMA prevalence in Rwanda (70.2%) (Ndahetuye et al, 2019) Uganda (86.2%) (Abrahmsén, Persson, Kanyima, & Båge, 2014) Kenya (64.0%) (Mureithi & Njuguna, 2016) and Ethiopia (59.2%) (Abebe, Hatiya, Abera, Megersa, & Asmare, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Mastitis in dairy cows is considered as one of the most important diseases resulting in poor production and reproductive efficiency (Ahmadzadeh et al, 2009;Halasa, Huijps, Østerås, & Hogeveen, 2007;Komba & Kashoma, 2020) and affecting herd profitability and sustainability (Dolecheck, García-Guerra, & Moraes, 2019). Mastitis is an inflammation of mammary glands and may be clinical or subclinical mastitis (SCMA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence rate of PR was reported as 12.3% in Iran (Mahnani et al, 2021b), 10.4% in Tanzania (Komba and Kashoma, 2020), 8.8% in France (Fourichon et al, 2001b), 7.8% in USA (Goff, 2006), 6.6% in Netherlands (Joosten et al, 1987), 6.5% in Denmark (Bruun et al, 2002), 6.1% in India (Deka et al, 2021), 3-6% in England (Esslemont and Kossibati, 1996), 3.1% in Australia (Stevenson, 2000). So, the incidence rate of PR in Turkey is nearly at an average level.…”
Section: Discussionmentioning
confidence: 99%
“…Our overall net loss estimates due to abortion in livestock in Tanzania of $131 million are about one-third of annual national loss due to Tick Born Diseases (TBD) estimated at $364 million by Kivaria in 2006(Kivaria, 2006. Foot and mouth disease was estimated to cause annual burden ranging between $351,000 and $531,000 (Häsler et al, 2021), mastitis was estimated to cause $4,700 with an estimated loss of $21.5 per quarter (Komba and Kashoma, 2020) and PPR was estimated to cause direct economic loss of $19.1 million in sheep and goats in one region of Kenya (Kihu et al, 2015)…”
Section: Aggregate Level Losses For Northern and All Of Tanzaniamentioning
confidence: 97%